Comparative Experimental Study on Torsional Behavior of RC Beam Using CFRP and GFRP Fabric Wrapping. (2016) - Tibhe, Shraddha B.; Rathi, Vijaykumar R.
Abstract: Fiber reinforced polymer (FRP) as an external reinforcement is used extensively to enhance the strength requirement related to flexure and shear in structural systems. But the strengthening of members subjected to torsion is yet to be explored as Torsion failure is a brittle form of failure. In present experimental study deals with the torsional strengthening of Reinforced Concrete beams using epoxy bonded Fiber- Reinforced Polymer (FRP) fabric. Total Thirty nine rectangular beams of size 150 mm × 300 mm and 1200 in length are casted. Out of which, three beams are control beam and remaining thirty six beams are classified into two groups. One with CFRP fabric wrapping and another with GFRP fabric wrapping. With various wrapping patterns. The applied CFRP and GFRP configurations are U-jacketed, vertical strips with spacing, and edge strips along with vertical strips along its entire length. Torsional capacity of beams of two groups is compared with control specimen with respect to torsional moment, angle of twist and ductility factor and it was observed that CFRP fabric bonded beam shows more torsional strength than the GFRP bonded beam.